Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 5,1: Briefe 1812-1837. Teil 1: Text (Edition) - Eke, Norbert Otto; Vizkelety, András; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Flankenspielorientierte Einstellung der Hypoid- und Kegelradgetriebe - Zimmer, Detmar

Konzepte einer Software-Architektur-Beschreibungssprache - Ebert, Jürgen; Engels, Gregor (Software-Entwicklung: Konzepte, Erfahrungen, Perspektiven, Fachtagung, 1989, Marburg (Germany))

CADDY-O: Syntaxgestütztes, graphisches Entwerfen konzeptioneller Datenbankschemata - Engels, Gregor (Tagungsband GI-Fachtagung "Interaktive Schnittstellen für Informationssysteme", TU Clausthal, Notizen zu Interaktive Systeme)

CADDY: Computer-Aided Design of Non-Standard Databases - Engels, Gregor; Hohenstein, Uwe; Hülsmann, Klaus; Löhr-Richter, Perdita; Ehrich, Hans-Dietrich (Proceedings of the International Conference on System Development Environments & Factories, Berlin, Germany)

Benutzerschnittstelle und Architektur der integrierten Datenbankentwurfsumgebung CADDY (Kurzfassung) - Engels, Gregor

Programmentwicklungsumgebungen: Konzepte und Realisierung - Engels, Gregor; Schäfer, Wilhelm

Computational methods for bifurcation problems with symmetries—with special attention to steady state and Hopf bifurcation points - Dellnitz, Michael; Werner, Bodo (Journal of Computational and Applied Mathematics)

On computations with integer division - Just, Bettina; Meyer auf der Heide, Friedhelm; Wigderson, Avi (RAIRO - Theoretical Informatics and Applications)

An optimal parallel dictionary - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the first annual ACM symposium on Parallel algorithms and architectures - SPAA '89)

On genuinely time bounded computations - Meyer auf der Heide, Friedhelm (STACS 89)

Time-optimal simulations of networks by universal parallel computers - Meyer auf der Heide, Friedhelm; Wanka, Rolf (STACS 89)

Computing minimum spanning forests on 1- and 2-dimensional processor arrays - Meyer auf der Heide, Friedhelm (STACS 89)

ODICE: Object-Oriented Hardware Description in CAD Environment - Rammig, Franz Josef; Müller, Wolfgang (Proc. of the Ninth IFIP Symposium on CHDLs and their Application)

Perspektiven für die Logikprogrammierung - Kleine Büning, Hans; Lettmann, Theodor (Workshop Wissensrepräsentation in Expertensystemen)

A Highly Integrated Tool Set for Program Development Support - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of the conference on ACM SIGSMALL/PC symposium on ACTES (SIGSMALL 1988), Cannes (France))
This paper describes the design of the integrated user interface of the software development environment IPSEN (Integrated Programming Support Environment). We explain the characteristic features of the IPSEN user interface, namely the structured layout of the screen, the command-driven tool activation, and especially the highly integrated use of the IPSEN tool set. We demonstrate those features by taking a sample set of tools of the IPSEN environment. That tool set supports all the programming-in-the-small activities within IPSEN. Finally, we sketch the realization of two prototypes running on an IBM-AT and a net of SUN workstations.

Konzeption einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Neugebauer, Leonore; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of DBTA/SI Data Dictionaries und Entwicklungswerkzeuge für Datenbank-Anwendungen, Zürich, Switzerland)

Auf dem Weg zu einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of the GI-Workshop on "Sprachspezifische Programmierumgebungen")

Ein Konzept zur Beschreibung von Software-Architekturen - Ebert, Jürgen; Engels, Gregor

Die Benutzerschnittstelle einer integrierten Modula-2 Programmentwicklungsumgebung - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of GI-Workshop Sprachspezifische Programmierumgebungen, Darmstadt, Germany)